On the assessment of CFD methods for vortical flows - Gonzales, Roberto; Prince, Simon A. (International Council of the Aeronautical Sciences (ICAS), 2021)
In this study, a general assessment was made on the capabilities of a wide range of turbulence models – both linear and non-linear eddy viscosity models, and simulation techniques to predict the process of vortex formation, growth and breakdown on a series of models at a range of Mach numbers (subsonic, transonic and supersonic) and angles of attack. The analysis was made on isolated components as a first approach to study the aerodynamics of a high-speed vehicle concept and used experimental data as the basis for a detailed validation exercise. These components included a family of slender axisymmetric bodies, a family of delta wings with different leading-edge radii and a double delta wing with different edge fillet configurations. Individual studies were made on each component, and different simulation approaches were used on each of them. It was found that the most accurate turbulence models were the k-e Realisable and k-w SST models, while the Scale Adaptive Simulation method was found to be the most accurate scale resolving turbulence approach.
© The Author.
Keywords: Vortex simulation; CFD; Delta Wings; Axisymmetric bodies